Influence of Sorbent Characteristics on Fouling and Deposition in Circulating Fluid Bed Boilers Firing High Sulfur Indian Lignite - Selvakumaran Palaniswamy; M. Rajavel; A. Leela Vinodhan; B. Ravi Kumar; A. Lawrence; A. K. Bakthavatsalam (Journal of Combustion)
125 MWe circulating fluidized bed combustion (CFBC) boiler experienced severe fouling in backpass of the boiler leading to obstruction of gas flow passage, while using high sulfur lignite with sorbent, calcium carbonate, to capture sulfur dioxide. Optical microscopy of the hard deposits showed mainly anhydrite (CaSO4) and absence of intermediate phases such as calcium oxide or presence of sulfate rims on decarbonated limestone. It is hypothesized that loose unreacted calcium oxides that settle on tubes are subjected to recarbonation and further extended sulfation resulting in hard deposits. Foul probe tests were conducted in selected locations of backpass for five different compositions of lignite, with varied high sulfur and ash contents supplied from the mines along with necessary rates of sorbent limestone to control SO2, and the deposits build-up rate was determined. The deposit build-up was found increasing, with increase in ash content of lignite, sorbent addition, and percentage of fines in limestone. Remedial measures and field modifications to dislodge deposits on heat transfer surfaces, to handle the deposits in ash conveying system, and to control sorbent fines from the milling circuit are explained.